2004
DOI: 10.1385/abab:112:2:101
|View full text |Cite
|
Sign up to set email alerts
|

Functional Sulfur Amino Acid Production and Seawater Remediation System by Sterile <I>Ulva</I> sp. (Chlorophyta)

Abstract: Sterile Ulva, which is a macroalga, has the potential to grow stably; therefore, this seaweed is expected to be an efficient resource of functional food containing various nutrients such as sulfur amino acids, proteins, carbohydrates, and minerals. Ulva latuca was selected from the "Marine Park" in Tokyo Bay, and its growth rate (g-dry/[m2.d]) was measured using model reactors located on the land or on the surface of the sea at Yokohama. The growth rate of U. lactuca was recorded to be approx 20 g-dry/(m2.d), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Following the success of on‐land photobioreactors in providing high biomass yields when the major cultivation parameters of temperature, light, mixing, and nutrients were controlled, theoretically possible intensified offshore cultivation methods were proposed . However, to the best of our knowledge, the intensification methods that control key parameters offshore, have not been demonstrated in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Following the success of on‐land photobioreactors in providing high biomass yields when the major cultivation parameters of temperature, light, mixing, and nutrients were controlled, theoretically possible intensified offshore cultivation methods were proposed . However, to the best of our knowledge, the intensification methods that control key parameters offshore, have not been demonstrated in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to ascertain the technical potential of producing biobutanol from algae that naturally grows in nutrient contaminated rivers, lakes, and bays. Of major concern is the removal of excess dissolved nitrates and phosphates [1–7], carbon dioxide [8–25] and heavy metals [26–30]. This study also compared butanol production from the classic acetone‐buanol‐ethanol (ABE) fermentation and the two step fermentation process.…”
Section: Introductionmentioning
confidence: 99%
“…Levels up to 5 g kg −1 have been isolated from the green alga Ulva lactuca , leading to a proposal for its cultivation as a source of cysteinolic acid anticipating its potential for treating hypertriglyceridemia, hyperlipidemia and obesity related diseases. 6 In all animal species cysteinolic acid was isolated in lower concentrations, 23–163 mg kg −1 for crustaceans and ray-finned fish, 20 and 6 mg kg −1 for the starfish Asterina pectinifera , 19 and taurine was usually more abundant than cysteinolic acid in animals. The lower concentrations of cysteinolic acid isolated from animals relative to algae suggests that it may arise from dietary ingestion, a suggestion consistent with the absence of bile acid conjugates of cysteinolic acid in some aquafarmed fish versus its presence in the same fish species when wild-caught ( vide infra ).…”
Section: Distribution Of D-cysteinolic Acid In the Biospherementioning
confidence: 99%
“…14 Cysteinolic acid is also found in most brown, green and red alga. 6,7,[15][16][17][18] A limited study suggested no variation in cysteinolic acid levels across a two month observation period in the red algae Chondrus ocellatus. 18 Cysteinolic acid was not detected in cyanobacteria in a survey of nine species.…”
Section: Distribution Of D-cysteinolic Acid In the Biospherementioning
confidence: 99%
See 1 more Smart Citation